'Garden White' Caladium - a University of Florida Cultivar for Sunny Landscapes and Large Containers - Zhanao Deng; Brent K. Harbaugh (EDIS)
ENH 1041, a 6-page illustrated fact sheet by Zhanao Deng and Brent K. Harbaugh, introduces tuber producers to this new extremely vigorous, large-leaved, tall white fancy-leafed caladium cultivar for sunny landscapes and large containers. Published by the UF Department of Environmental Horticulture, June 2006.